Case report: Congenital multidrug-resistant tuberculosis - Zhang, Hongyi; Xia, Lu; Zhang, Peize (Frontiers in Tuberculosis, 2024)
Congenital multidrug-resistant tuberculosis (MDR-TB) is a rare disease with high mortality. We report a case of a neonate girl with congenital MDR-TB. The infant's mother underwent in vitro fertilization–embryo transfer and did not show any symptoms prior to delivery. After the 14th day of life, the infant had a fever and worsening difficulty breathing despite antibiotic treatment. She was then confirmed to have congenital MDR-TB and received ventilation and anti-TB treatment. When the infant's TB was diagnosed, her mother was screened for TB and found to have MDR-TB, affecting both her lungs and reproductive system. They both recovered and were discharged from the hospital, with anti-TB treatment ongoing.